Motion of a polymer globule with Vicsek-like activity: from super-diffusive to ballistic behavior. Issue 3 (3rd July 2021) - Paul, Subhajit; Majumder, Suman; Janke, Wolfhard
ABSTRACT: Via molecular dynamics simulation with Langevin thermostat we study the structure and dynamics of a flexible bead-spring active polymer model after a quench from good to poor solvent conditions. The self propulsion is introduced via a Vicsek-like alignment activity rule which works on each individual monomer in addition to the standard attractive and repulsive interactions among the monomeric beads. We observe that the final conformations are in the globular phase for the passive as well as for all the active cases. By calculating the bond length distribution, radial distribution function, etc., we show that the kinetics and also the microscopic details of these pseudo equilibrium globular conformations are not the same in all the cases. Moreover, the center-of-mass of the polymer shows a more directed trajectory during its motion and the behavior of the mean-squared-displacement gradually changes from super-diffusive to ballistic under the influence of the active force in contrast to the diffusive behavior in the passive case.